Desempeño laboral de los empleados de la Cooperativa de Transportes CITAM - Parra Cercado, Robert Yefferson (2021)
The CITAM cooperative was founded in the city of Montalvo on March 24, 1972, within the place is broken down its hierarchical order that make up the space for the operation of the same. The objective of this case study is to analyze the different causes that intervene in the scarce commitment of the collaborators and the existing inefficiency in the activities that they must develop within the CITAM cooperative. For this research, a survey consisting of 8 multiple-choice questions was applied as a technique. It is also mentioned that the sub-line of research is the Administrative Management Model of the Commercial Engineering Career. The results showed that most of them do not comply with the safety standards, they do not always have all the materials to work with peace of mind, they do not always receive incentives for the work they do, and they do not comply with the vacation time that should be granted to employees. In conclusion, the problems that have arisen in the CITAM cooperative are linked to the work performance of the workers of these organizations, the same problems that have directly affected the clients or users who are the main base of the services provided by the cooperative.